Pancreatic resection for cancer: the Heidelberg technique - Schneider, Martin; Strobel, Oliver; Hackert, Thilo; Büchler, Markus W. (Langenbeck's archives of surgery, 2019)
Pancreatic cancer is associated with high recurrence rates, and any surgery should aim to prevent local recurrence. However, systematic resection of putatively tumor-infiltrated soft tissue adjacent to the celiac branches and superior mesenteric artery has not regularly been applied in pancreatic head resection.